Nicaragua's Red de Protección Social: An exemplary but short-lived conditional cash transfer programme - Charity Moore (International Policy Centre for Inclusive Growth (IPC-IG), 2009)
This country study investigates the history and eventual conclusion of Nicaragua's conditional cash transfer programme, the Red de Protección Social (RPS). Specific features of the programme, in both its first and second phase, are described thoroughly to provide readers with an appropriate understanding and appreciation of the details of RPS. A brief overview of the current state of social protection in Nicaragua is also included to enhance understanding of the current environment in the country. In particular, this study discusses the elements that contributed to the programme's successes and eventual discontinuation. Although RPS achieved most of its goals, it was unable to garner enough domestic support to ensure its continuation. While the programme was known internationally for the positive effects it quickly had on children's health and education, its purpose and performance were misunderstood at the domestic level. This lack of appreciation heightened criticisms of RPS and hindered support for the programme within its institutional base. RPS is an example of an efficient and effective conditional cash transfer programme, but it also serves as a warning to officials operating in similar contexts. RPS officials had to balance the demands of domestic and international stakeholders, meeting short-term goals while ensuring the initiative's longterm viability. The Nicaraguan experience usefully illustrates the challenges involved in creating an exemplary programme and ensuring its long-term sustainability.
Keywords: 330